"Agape love is justice": Black clergies' public and theological support of Black gay men. Issue 9 (3rd August 2022) - Miller, Robert L.
Abstract: This study explored how 60 Black clergy came to publicly and theologically support Black gay men. They participated in three 90-minute life history interviews to address the study aims. Open, axial and selective coding were used to understand and order themes within their accounts while addressing specific aims. Life events, purpose-driven theological training and a commitment to justice provide the basis for theological and public support of Black gay men. Clergies' understanding of justice is an expression of agape love. Such love inspires both the support and advocacy of stigmatised, marginalised and overly burdened populations. Study findings question monolithic understandings of both Black clergy and the Black church as homophobic and heteronormative. The informants' data reveal agape love as a key motivation of ministerial holistic support for marginalised and oppressed populations, including Black gay men. Finally, these data assert that agape love is inconsistent with heteronomative and homophobic scriptural interpretation.